Shooting efficiency for winners of World Cup and World Championship races in men`s and women`s biathlon: where is the cut-off? - Björklund, G. (International Journal of Performance Analysis in Sport, 2018)
The shooting profile of the biathlete is presented as the mean shooting percentage, which lacks valuable information for performance profiling. Hence, the aim of the study was to present a way of profiling biathlete shooting efficiency and profiling the men`s and women`s winners in the IBU World Cup and World Championships to clarify the fewest hits necessary to win races. Data from 106 competitions from two seasons were analysed and dichotomised. The proportions (p) (miss/hit) and 90% confidence interval were estimated, and binominal distributions for overall, standing and prone shooting. The women`s winners showed higher overall shooting efficiency than the men`s winners (-5.4 to -0.4 90%CI) season 2015/2016, due to lower prone shooting efficiency for the men. The men increased their overall shooting efficiency for the 2016/2017 season, compared to 2015/2016, due to increased prone shooting accuracy (-6.9 to -0.2 90%CI). The likelihood of winners missing three targets went from 14.7% to 3.7% and 3.5% to 4.3% for the 2015/2016 to 2016/2017 season for men and women, respectively. Overall, the men varied more than women between seasons due to reduced prone shooting efficiency, while the third miss appeared most critical for performance.